Factors related to sexual behavior among adolescents - Dian Thiofanny Sopacua; Citra Windani Mambang Sari; Habsyah Saparidah Agustina; Damar Irza; Laili Rahayuwati (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: One of the problems in adolescents is sexual behavior, which generally begins with the courtship process and behavior in dating. Purpose: The study aimed to determine the factors associated with sexual behavior in adolescents.Methods: This study used secondary data and analyzed using a cross-sectional design on a sample of 429 adolescents. Quantitative data used the chi-square test.Results: One of the factors related to dating behavior is age, which is proven that dating behaviors such as holding hands (p=0.037), hugging (p=0.002), kissing lips (p=0.041), while touching/stimulating and having sexual relations are not related to age factor (p=0.929). Factors such as gender, education level, area of residence and information exposure were not related to dating behavior.Conclusions: There is a relationship between age factors and dating behavior in adolescents. Cross-sectoral collaboration, the use of digital media for socialization and education, and strengthening family and religious functions are strategies used to develop youth health programs.